Late Miocene amphibians and reptiles: new insight into the pre-Messinian herpetofaunas in Turkey. (3rd October 2022) - Syromyatnikova, Elena; Mayda, Serdar; Tesakov, Alexey
ABSTRACT: The herpetofauna of the late Miocene age in Turkey is nearly unknown, as it is represented by a single known anguine assemblage from the latest Miocene of Süleymanli locality. The amphibians and reptiles from the three early late Miocene (MN 9) localities of Bayraktepe 2, Kütahya, and Altıntaş in Anatolia are described here. One amphibian ( Latonia spp.) and five squamate ( Pseudopus sp., Varanus sp., Colubrinae indet. 1 and 2, and Naja sp.) taxa are revealed. The Bayraktepe 2 and Kütahya localities are dominated by anuran remains, and exclusively Latonia, whereas the Altıntaş locality is represented by reptilian taxa. Although the material is relatively poor, it provides the first information about the late Miocene assemblage of amphibians and reptiles in Turkey. The records of Naja and Varanus from Altıntaş are currently the oldest records of these taxa in Anatolia.